In search of an equitable, sustainable globalization : the bittersweet dilemma - Samli, A. Coskun (Quorum Books, 2002)
Annotation Globalization is often described as "Darwinism on steroids" and is a force to be reckoned with. Its goal to improve the economic status of underdeveloped areas of the world is noble enough, but left unchecked, globalization is not always fair and equitable in its practices and outcomes. This widens the gap between rich and poor nations. Samli argues that Third World countries must learn to take advantage of globalization and learn to protect themselves against its darker forces. This book presents what Samli calls "countermarginalization," a process that includes such strategies and tactics as partnering, networking, and entrepreneurship. Samli explains how emerging countries of the world can develop their own means of growth to counter the risk of marginalization, arguing that entrepreneurship is essential and needs to be nurtured. This book provides a thoughtful source of discussion and learning, offering a new perspective on the big questions that won't just go away, despite certain efforts to ignore them.